Argentine Jews or Jewish Argentines? : essays on ethnicity, identity, and diaspora - Rein, Raanan, 1960- (Jewish identities in a changing world, 2010)
This volume is devoted to Jewish Argentines in the twentieth century, and deliberately avoids restrictive or prescriptive definitions of Jews and Judaism. Instead, it focuses on people whose identities include a Jewish component, irrespective of social class and gender, and regardless of whether they are religious or secular, Ashkenazi or Sephardic, or affiliated with the organized Jewish community.